Political Betrayal of Education - Rifqah Ramadhana Jufri; Andi Neneng Nurfauziah; Herwanita Herwanita (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
The deteriorating practice of scientific elaboration in education is often associated with the increasing information overload in the digital social space. This condition not only impacts the quality of knowledge production but also weakens individuals' reflective capacity to interpret their roles and the educational ecosystem. In this context, educational actors tend to be mired in ambivalence, on the one hand as actors, but on the other as victims of malpractice, related information, and increasingly problematic educational political policies. Hence, the author conceived the research title "Political Betrayal of Education. Furthermore, excessive administrative pressure also reflects the intellectual space available for educators and students to elaborate on fundamental issues in education. Consequently, the orientation of education has shifted from strengthening critical reasoning to fulfilling procedural administrative indicators. This phenomenon is reflected in the rise in various forms of academic misconduct, including plagiarism, bribery in exams, grade-buying, cheating, sexual violence in educational settings, and the prevalence of practicums in scientific publications involving various academic levels, from students to professors. Furthermore, actions against criticism are often legitimized by authoritative institutions through various forms of intimidation, both symbolic and physical. This further emphasizes the dysfunction of education as a space for developing critical thinking. In this development, education has experienced a reduction in function, from its original role as a locomotive of knowledge-based social transformation. Now, it has become a commodified entity vulnerable to domination practices resembling intellectual thuggery. Based on this background, this research aims to deeply examine the empirical dynamics in educational practices and analyze their implications for national education policy. Furthermore, this research seeks to reconstruct the function of education as a "brahmana," namely, as an entity possessing moral and intellectual authority in establishing independent and sovereign social control mechanisms, both at the institutional level and in society at large.